Peptidomimetic nitrile inhibitors of malarial protease falcipain-2 with high selectivity against human cathepsins. Issue 9 (15th May 2018) - Nizi, Emanuela; Sferrazza, Alessio; Fabbrini, Danilo; Nardi, Valentina; Andreini, Matteo; Graziani, Rita; Gennari, Nadia; Bresciani, Alberto; Paonessa, Giacomo; Harper, Steven
Graphical abstract: Abstract: Falcipain-2 (FP2) is an essential enzyme in the lifecycle of malaria parasites such as Plasmodium falciparum, and its inhibition is viewed as an attractive mechanism of action for new anti-malarial agents. Selective inhibition of FP2 with respect to a family of human cysteine proteases (that include cathepsins B, K, L and S) is likely to be required for the development of agents targeting FP2. Here we describe a series of P 2-modified aminonitrile based inhibitors of FP2 that provide a clear strategy toward addressing selectivity for the P. falciparum and show that it can provide potent FP2 inhibitors with strong selectivity against all four of these human cathepsin isoforms.